2010
DOI: 10.1021/ac101473g
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Coatings for the Study of Polycation/Multicharged Anion Interactions by Capillary Electrophoresis: Application to Dendrigraft Poly-l-lysines with Negatively Multicharged Molecules

Abstract: The study of interactions between oppositely multicharged (macro)molecules remains a challenging issue. In frontal analysis capillary electrophoresis (FACE), it is difficult to avoid the adsorption of one of the interacting partners onto the capillary wall. In this work, we demonstrate the possibility to use FACE and affinity capillary electrophoresis (ACE) on a neutrally coated capillary for the study of interactions between a polycationic dendrigraft (or linear) poly-l-lysines, on one hand, and a multicharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…It was previously reported that adsorption of PLL on various substrates is controlled by the balance of electrostatic and nonelectrostatic interactions (Choi et al, 2015). In the current work, the adsorption was most likely driven by the entropy gain due to release of counterions during adsorption of oppositely charged components, but hydrophobic interactions between PLL and wax particles may have also played a role (Choi et al, 2015;Zou, Oukacine, Le Saux, & Cottet, 2010). Upon rinsing with water, a slight decrease in sensed mass of PLL was observed, likely deriving from the removal of some loosely bound molecules.…”
Section: Model Studies On Ultrathin Cnf Filmsmentioning
confidence: 66%
“…It was previously reported that adsorption of PLL on various substrates is controlled by the balance of electrostatic and nonelectrostatic interactions (Choi et al, 2015). In the current work, the adsorption was most likely driven by the entropy gain due to release of counterions during adsorption of oppositely charged components, but hydrophobic interactions between PLL and wax particles may have also played a role (Choi et al, 2015;Zou, Oukacine, Le Saux, & Cottet, 2010). Upon rinsing with water, a slight decrease in sensed mass of PLL was observed, likely deriving from the removal of some loosely bound molecules.…”
Section: Model Studies On Ultrathin Cnf Filmsmentioning
confidence: 66%
“…However, the adsorption of the interacting species on the capillary wall has been identified as a major concern . To overcome this problem, CE‐FA in capillary with a neutral coating has been developed . Since there is a very weak or none existing EOF in a neutral coated capillary, it is impossible to let all interacting species migrate with only an electrical potential applied to the capillary.…”
Section: Resultsmentioning
confidence: 99%
“…Among the neutral polymers, four have proven their high efficiency to coat the capillary and then to avoid protein adsorption: the cellulose derivatives, the polyvinylalcohol (PVA), the polyethylene oxide (PEO) and the acrylamide-based polymers [27,28] or copolymers [29]. We chose to study the performance of a covalently-linked HPC capillary, previously used in our laboratory [30], and two physically adsorbed coated capillaries using PEO and PDMA.…”
Section: Evaluation Of Neutral Coatingsmentioning
confidence: 99%